2017
DOI: 10.3390/ijerph14040407
|View full text |Cite
|
Sign up to set email alerts
|

Soil Lead and Children’s Blood Lead Disparities in Pre- and Post-Hurricane Katrina New Orleans (USA)

Abstract: This study appraises New Orleans soil lead and children’s lead exposure before and ten years after Hurricane Katrina flooded the city. Introduction: Early childhood exposure to lead is associated with lifelong and multiple health, learning, and behavioral disorders. Lead exposure is an important factor hindering the long-term resilience and sustainability of communities. Lead exposure disproportionately affects low socioeconomic status of communities. No safe lead exposure is known and the common intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Moreover, a recent review of the scientific literature on Pb by Vorvolakos et al [ 7 ] found that there is no safe threshold for Pb exposure. Other studies and the ATSDR confirm this finding [ 1 , 2 ]. Landrigan et al [ 8 ] estimated the contribution of environmental pollutants to the incidence, prevalence, mortality, and costs of pediatric disease in American children and estimated the total annual costs for Pb poisoning to be $43.4 billion.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Moreover, a recent review of the scientific literature on Pb by Vorvolakos et al [ 7 ] found that there is no safe threshold for Pb exposure. Other studies and the ATSDR confirm this finding [ 1 , 2 ]. Landrigan et al [ 8 ] estimated the contribution of environmental pollutants to the incidence, prevalence, mortality, and costs of pediatric disease in American children and estimated the total annual costs for Pb poisoning to be $43.4 billion.…”
Section: Introductionsupporting
confidence: 74%
“…The ATSDR also described that many children diagnosed with LDs as a consequence of Pb exposure perform poorly in school [ 1 ]. Previous studies suggest a significant relationship between Pb exposure and LDs [ 1 , 2 ]. For example, Kaiser et al [ 3 ] used extant datasets from the Florida Department of Health, Childhood Lead Poisoning Prevention Program and the Florida Department of Education to compare children who were tested for Pb poisoning to children not tested for Pb poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Drip zones are the 1 meter zone immediately surrounding structures containing Pb paint where it has naturally or purposefully been removed to collect in the surrounding soil. Houses in other cities have shown a similar pattern including Indianapolis, Indiana (Filippelli et al, 2005); London, England (BGS, 2017), New Orleans, Louisiana (Mielke et al, 2017), and Sydney, Australia (Birch et al, 2011).…”
Section: Introductionmentioning
confidence: 89%
“…Another study (1%) conducted network medicine analysis of specific comorbidities [114]. Two studies [115,116] (2%) were similar in design, looking at pre-, and post-Katrina-induced changes in the environmental (soil) and blood signatures of lead for the affected communities. Finally, another study (1%) conducted a secondary analysis of geochemical maps and cancer data at the municipality level [117].…”
Section: Description Of the Selected Articlesmentioning
confidence: 99%
“…Four studies (5%) described the characteristics of exposome cohorts [53,127,72,55] and another (1%) characterized urban environmental and health indicators using the urban exposome framework [73]. Four studies (5%) explored the partitioning of a contaminant between environmental and human biospecimen, of which three considered a biomarker of exposure to environmental contaminants as a study outcome [117,115,80,116] , while only one study (1%) linked occupational records to health outcomes [109].…”
Section: Interventionsmentioning
confidence: 99%